Aquatic Coleoptera from two protected areas of the Humid Chaco eco-region (Chaco Province, Argentina) - Libonatti, María Laura (2013)
A list of the species of aquatic Coleoptera inhabiting Chaco National Park and El Cachapé Wildlife Refuge, two protected areas located in the Humid Chaco eco-region, is presented for the first time. One hundred and twenty-two species included in 45 genera and 10 families were identified. Two species are new for Argentina: Ora atroapicalis Pic and Ora semibrunnea Pic (Scirtidae). Ten genera (Dytiscidae: Anodocheilus Babington, Bidessonotus Régimbart, Hemibidessus Zimmermann; Noteridae: Mesonoterus Sharp, Notomicrus Sharp; Hydraenidae: Hydraena Kugelann, Gymnochthebius Orchymont; Hydrophilidae: Chasmogenus Sharp, Chaetarthria Stephens; Scirtidae: Ora Clark, Scirtes Illiger) and 41 species are first cited from Chaco Province. The high diversity of aquatic Coleoptera recorded highlights the importance of these protected areas.